Placeringen av idiom i ordboksartiklar. Ett mikrostrukturellt problem - Malmgren, Sven-Göran; Sköldberg, Emma (Nordiske Studier i Leksikografi, 2010)
In this paper, we discuss the placing of idioms in general defining dictionaries. Rejecting the idea of making idioms autonomous entries, and postulating that the problem of entry address is solved (e.g., the idiom may be placed in the entry corresponding to the first noun of the idiom), we focus on the following problem: should all idioms be gathered at the end of the entry, or should they be distributed among the different numbered senses of the entry? The corresponding structures may be called non-integrated and integrated, respectively. We make the following claims. In elementary learners’ dictionaries, the non-integrated structure is preferable, since it facilitates the user’s job of simply finding the idiom. However, in more advanced learners’ dictionaries, it may be a good idea to make use of the integrated structure, since this gives an extra learning effect; the user will, in many cases, find (semantically) related idioms close to the idiom (s)he is looking for. The same holds for comprehensive L1 dictionaries. It should also be noted that such dictionaries fulfil a documentary function, and thus, the description of the vocabulary should be as good as possible from a lexicological point of view.